Generative Learning Strategy is a Solution for Teaching Writing Skill - Ferri Susanto (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
The purpose of this research was to determine the implementation of the Generative Learning strategy model as a solution for teaching text writing skills in English and to develop meaning construction, associations between stimulus and knowledge, beliefs and experiences in the new normal in the midst of the COVID-19 pandemic. This research discussedd the application of the Generative Learning Strategy Model which also aims to improve the ability to write texts for second semester students of the 2021/2022 academic year. This research was classroom action research that used 2 cycles. The research subjects consisted of 35 students, 25 female students and 10 male students. The instruments were developed by valid questionaires with significan 0,000 < 0,005 and reliability ststistic at the cronbach’s Alpha 0,782 > 0,73 so the data were realiable. For supporting these data, this reaserach also used observation sheets, interviews and documentations. This research was carried out in two cycles which included planning, action, observation and reflection. Based on the written test, there was a better improvement from pre-assessment 68.60, cycle I 72.60 increased to 79.92 cycle II. The increase obtained from testing is 4.54 points. This shows that the Generative Learning Model strategy can improve the ability to write texts.